(untitled) (Research, Society and Development, 2022)
Empowerment is a health promotion principle to be followed and an objective to be achieved in different scenarios. Although widely used, its understanding is complex. This study aimed to analyze the perception of professionals and users about the term empowerment. This is qualitative research with focus groups with workers and users of a SUS health promotion program. Content analysis was performed. The results showed that the understanding of the term is different between workers and users. For the professional, the term is purified by the familiarity with the political and theoretical discourse, while the users’ speeches are permeated by subjectivities and affective reports. Thus, perceptions allow updating the term as a process and related to the connection between political and subjective dimensions, without the polarization between individual and collective. Empowerment, as recognition of the power of subjects to make choices, does not end in itself, it always occurs in exchanges, in the relationship with the other, which are built daily. That is why the importance of creating scenarios or environments that allow the subject to recognize himself in the encounter with the other, as potentially inventive spaces. It is up to professionals to create scenarios in which exchange relationships can exist so that these powers emerge.